Natural history and impact of treatment with tafamidis on major cardiovascular outcome‐free survival time in a cohort of patients with transthyretin amyloidosis. (9th November 2020) - Bézard, Mélanie; Kharoubi, Mounira; Galat, Arnault; Poullot, Elsa; Guendouz, Soulef; Fanen, Pascale; Funalot, Benoit; Moktefi, Anissa; Lefaucheur, Jean‐Pascal; Abulizi, Mukedaisi; Deux, Jean‐François; Gendre, Thierry; et al.
Abstract: Aims: Hereditary (ATTRv) and wild‐type (ATTRwt) transthyretin amyloidosis are severe and fatal systemic diseases, characterised by amyloid fibrillar accumulation principally in the heart or peripheral nerves (or both). Since 2012, tafamidis has been used in France to treat patients with ATTRv with neuropathy (alone or combined with cardiomyopathy). Recently, the Phase III ATTR‐ACT trial showed that tafamidis decreased the relative risk of mortality in ATTR amyloidosis with cardiomyopathy. The aims of this study were to assess the clinical characteristics of ATTR amyloidosis in a real‐life population in comparison to the population included in the ATTR‐ACT trial and to assess the impact of tafamidis treatment on major cardiovascular outcome (MCO)‐free survival time without cardiac decompensation, heart transplant, or death. Methods and results: From June 2008 to November 2018, 648 patients with ATTR amyloidosis (423 ATTRwt and 225 ATTRv) consecutively referred to the French Referral Center for cardiac amyloidosis were included. A total of 467 (72%) patients matched the inclusion criteria of the ATTR‐ACT trial. For the 631 patients with cardiomyopathy, tafamidis treatment was associated with a longer median MCO‐free survival time ( n  = 98): 1565 (1010–2400) days vs. 771 (686–895) days without treatment (log‐rank P  < 0.001). This association was confirmed after considering confounding factors (age at inclusion, N‐terminal pro‐B‐type natriuretic peptide and amyloidosis type) with a propensity score (hazard ratio 0.546; P  = 0.0132). Conclusion: In a large cohort of ATTRwt and ATTRv patients, representative of the inclusion criteria of the ATTR‐ACT trial, the present results show an association between tafamidis treatment and a lower occurrence of cardiovascular outcomes in a real‐life population. Abstract : Schematic representation of the main results describing the correspondence of ATTRACT trial selection with real‐life cohort and the impact of tafamidis treatment on major cardiovascular outcome‐free survival time in a cohort of patients with transthyretin amyloidosis.